INVESTIGATION OF COLMATATION REGULARITIES PERTAINING TO HIGHLY DISPERSED PARTICLES IN POROUS FIBROUS MATERIALS INFLUENCED BY ELECTRIC FIELD - M. V. Tumilovich; L. P. Pilinevich; V. I. Baikov; A. E. Galkin; T. V. Sidorovich (Наука и техника)
The theoretical analysis of regularities in colmatation of highly dispersed particles from gas streams in porous fibrous materials influenced by electric field has been carried out in the paper. The paper reveals  that the use of an electric field can significantly increase colmatation efficiency of highly dispersed dp < 0,5 µm sized particles and what is especially important that is colmatation efficiency of the most hard-to-capture dp ≈  0,3 μm sized particles. Its highest values are achieved in the case of charged particle filtration through charged fibers. The colmatation efficiency is increased with higher particle and fiber charge, higher  packaging density and specific surface and decrease of filtration speed.